La gestion du changement institutionnel en matière d'épandage agricole des boues d'épuration en France - Christophe Déprés; Dominique Vollet (Territoire en Mouvement)
"Independent Organizations" (IO) are an institutional change promoted by the french government to manage in a better the spreading in agriculture of sewage sludge from urban areas. It is shown that the emergence of such an institutional change, throughout a territory depends on both exogenous and endogenous factors. Two complementary approaches have been used: a quantitative first phase at a national scale, a second phase which is based on four case studies (departments: Ain, Haut-Rhin, Haute-Garonne, Aveyron) characterized by a variety of agricultural contexts, rural-urban linkages and water agencies. Exogenous factors including political decisions result in a supra-territorial, national and European levels. National water agencies exert indeed an important role in the setting-up of IO in two different ways: the strategy adopted by the agency or agencies involved in the water department and geographical location department covered by one, two or three water agencies.This phenomenon can be described as an induced institutional change, embodied in the ability of local action within specific territories such as learning effects resulting from past experiences nearby. The territorial coordination built under specification of agricultural and urban-rural relations represents a major endogenous explanatory factor. The activation process specific resources can play on two determinants of coordination between actors: the registers of the organizational and institutional coordination. Departmental case studies have confirmed that the vast diversity of local situations (especially in departments) in terms of the emergence of institutional innovations related to sludge management is explained well in the double pressure of endogenous and exogenous factors.